CORPORATE TAX AVOIDANCE AND ZOMBIE FIRMS IN BUMN COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Idris, Muh.; Mira, Mira; Indriana, Indriana (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study aims to analyze the effect of corporate tax avoidance on the zombie status of state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX). The research method used is a quantitative approach with a causal-comparative approach, using secondary data from SOE annual reports for the 2018–2022 period, analyzed using a fixed-effects panel data regression model. The results show that tax avoidance has a significant negative effect on the zombie status of firms, meaning that the higher the level of tax avoidance, the less likely the company is to be classified as a zombie. However, firm size and leverage have no significant effect, while profitability (ROA) shows a nearly significant negative effect. The conclusion of this study is that tax avoidance can act as a short-term fiscal efficiency strategy to reduce the potential for zombification, but it is not statistically strong enough to be a primary determinant in the context of SOEs in Indonesia, which have their own structural and governance characteristics. Keywords: Tax Avoidance, Zombie Firms, Soes, Fiscal Effectiveness, Panel Data